Judith and the Dragon: A Jesuit architectural relief from Gorgora Iyäsus church, 1626–1632 - Fernández, Víctor M.; de Torres, Jorge; Martinez d'Alòs-Moner, Andreu; Cañete, Carlos; Bausi, Alessandro; Belay, Gashaw (Aethiopica, 2015)
In the 2014 excavations at the Jesuit church of Gorgora Iyäsus on the northern shore of Lake Ṭana a remarkable relief in stone was unearthed. The relief was originally part of the church’s façade. It represents the biblical heroine Judith over a dragon and it contains two inscriptions in Gǝʿǝz from the Book of Judith and Genesis. This piece represents one of the few recorded inscriptions on stone from the end of the Aksumite period to the present time. The article focuses on the historical context that witnessed the production of this relief and provides an interpretation of its iconography.